MiR‐892a Promotes Hepatocellular Carcinoma Cells Proliferation and Invasion Through Targeting CD226. Issue 6 (29th December 2016) - Jia, Baoxing; Tan, Ludong; Jin, Zhe; Jiao, Yan; Fu, Yu; Liu, Yahui
ABSTRACT: Our study is aim to investigate the influence of miR‐892a on proliferative and invasive activities of human hepatocellular carcinoma (HCC) cells through regulating CD226 expression. QRT‐PCR was used to detect the expression levels of miR‐892a and CD226 mRNA in HCC tissues and adjacent tissues or HCC cells and normal cells whereas Western Blot was used to detect the CD226 protein expression in tissue and cell samples. Then HuH‐7 cell line was selected for following assays and respectively transfected with miR‐892a mimics, miR‐NC, Plenti‐GIII‐Ubc‐CD226, and Plenti‐GIII‐Ubc followed by qRT‐PCR assay to detect the miR‐892a and CD226 expression. The luciferase reporter assay was conducted to determine if miR‐892a directly targeted CD226 and then CCK‐8 assay, wound healing assay, Transwell assay, and flow cytometry were used to detect cell proliferation, migration, invasion ability, cell cycle, and cell apoptosis. What's more, relationships between expression levels of miR‐892a or CD226 and overall survival (OS) or disease‐free survival (DFS) of HCC patients were investigated based on TCGA database. MiR‐892a was high‐expressed in HCC tissues or cells while CD226 was low‐expressed. MiR‐892a directly targeted CD226 and up‐regulating miR‐892a expression could promote proliferative, migrating, and invasive activities of HCC cells. Different expression levels of miR‐892a and CD226 both related to the prognosis of HCC. MiR‐892a promotes hepatocellular carcinoma cells proliferation and invasion through regulating CD226 expression. J. Cell. Biochem. 118: 1489–1496, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Different expression levels of miR‐892a and CD226 both had influence on the prognosis of LC. MiR‐892a promotes liver cancer cells proliferation and invasion through up‐regulating CD226 expression.